IMPACT OF ARMED CONFLICT ON THE YOUTH OF KASHMIR - Peer Amir Ahmad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
For nearly three decades, Kashmir has "been suffering a chronic socio-political turmoil. Kashmir's social fabric has been torn apart by the ongoing fighting, which has impeded its physical infrastructure as well (creating social, economic and psychological problems). The strife in Kashmir has had devastating impacts, especially on the young people of the region. This report emphasises the extent to which the violence has impacted the lives of young people in Kashmir and their opportunities for gainful employment. As well as the impact that "violation of fundamental rights" has had on young people in Kashmir.